2019
DOI: 10.13189/ujph.2019.070204
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Threshold of the Finnish Diabetes Risk Score (Findrisc) for Screening at-Risk Adults in an African Population in Southern Benin

Abstract: This study aims to determine the performance of the FINDRISC tool for screening adults at risk for type2 diabetes in an African population in southern Benin. This retrospective study included 536 subjects aged 25 to 65 years. The FINDRISC questionnaire score was calculated using seven components: age, body mass index, waist circumference, regular practice of 30 minutes of physical activity, regular consumption of five portions of fruits and vegetables, the family history of diabetes and the presence of high bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Compared to the African studies, our prediction score threshold value was close to that of the Beninese study (≥8.5) in West Africa [26] and lower than that of the Algerian studies (≥13 for women and ≥11 for men) in North Africa [27] and Botswana (≥17) in Southern Africa [2].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Compared to the African studies, our prediction score threshold value was close to that of the Beninese study (≥8.5) in West Africa [26] and lower than that of the Algerian studies (≥13 for women and ≥11 for men) in North Africa [27] and Botswana (≥17) in Southern Africa [2].…”
Section: Discussionsupporting
confidence: 51%
“…In Africa, compared to our score of less than 7 (58.54%), Omech in Botswana [24], Olamoyegun in Nigeria [25] and Azzouz in Algeria [27] had lower scores of 15.1%, 14% and 7.9% respectively. While Metonnou-Adanhoume in Benin [26] reported a high score of 68.28%. These differences in the proportion of scores are methodological: small sample size for the Botswana study [24]; semi-urban setting for the Nigerian study versus urban [25]; retrospective collection with data from 2006 for the Benin study versus prospective [26].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our study, the majority of the participants at very highrisk were women (Table 1), and we found that being a woman increases the risk of diabetes by 1.95 times (p = 0.030) ( Table 2). In several studies, scale scores of women are higher than that of men, and being a woman increases the risk of diabetes [9,21,24,25]. In a Norwegian study, 12.1% of females were in the high-risk group, while this figure was 9.6% for males [18].…”
Section: Discussionmentioning
confidence: 95%